Dreamcatcher - King, Stephen (Hodder & Stoughton, 2011)
Once upon a time, in Derry, four young boys stood together and did a brave thing; something that changed them in ways they hardly understood. Twenty-five years later, they still meet once a year to go hunting in the woods - but this time a stranger stumbles into their camp.